Global trends in e-labeling: a comprehensive geographical perspective - Dangy-Caye, Agnès; Lebreton, Valentin; Lumsden, Rebecca; Faber, Sabine; Cavalli, Ana; De Lucia, Maria Lucia; Desai, Sima (Frontiers in Medicine, 2025)
IntroductionThis study presents a comprehensive analysis of e-labeling adoption for medicinal products worldwide. Electronic Product Information (ePI) makes available the most up to date approved medicinal product information on an electronic platform, accessed through a code or a locator included on the product packaging. Electronic Product Information can be viewable in different formats from simple ones (pdf file) to a more structured form allowing true digitalization (html/xml).MethodsThe data were recovered based on internal company survey data from 182 countries collected between January 2, 2024, and April 7, 2025.ResultsBased on data from 182 countries where the company operates, the findings reveal diverse implementation stages across regions, with some countries having fully incorporated e-labeling into their regulations while others explore initial pilot programs. The hybrid approach combining printed leaflets and electronic product information with some possibilities of removing the printed leaflet emerges as the predominant model in pilot studies, though most countries still mandate paper documentation. QR codes on outer packaging (74.7%) and PDF format (67.3%) represent the most widely adopted technical solutions for the implementation of e-labeling.DiscussionE-labeling offers substantial benefits including real-time information updates, environmental sustainability, and supply chain improvements. Cross-regional knowledge exchange and multi-stakeholder collaboration will be essential to accelerate harmonized global e-labeling adoption.